Microplastics Quantification in Meretrix lyrata through Rapid Screening Method using Nile Red - Eric Ngie Hao, Lau; Aazani, Mujahid; Cindy, Peter; Moritz, Müller (UNIMAS Publisher, 2025)
Microplastics have emerged as a significant form of plastic pollution. Many ingestions in biota were reported worldwide. Filter feeder such as bivalves are prone to microplastics ingestion due to the non-selective feeding behavior. Bivalves are usually consumed as whole, without gut removal, which can pose a threat towards human consumption. This study focused on Meretrix lyrata to examine the level of microplastics ingestion under two factors: size class and weather seasons. The rapid screening approach with the fluorescent tagging using Nile red on microplastics for biota samples was used to quantify M. lyrata samples (n = 81) in this study. The high lipid content of the clams presented a significant challenge to the effectiveness of the method. As an alternative, high temperatures from acidification were used to disrupt lipid membranes and improve extraction efficiency. A total of 15,867 microplastics were quantified, with the average microplastics ingestion of 195.90±43.6 items/individuals. The statistical analysis indicated that clam size had a significant effect on the rate of microplastics ingestion (p<0.05), whereas weather season did not show a significant effect (p>0.05). Polyvinylchloride (66.5%), polypropylene with silicate mix (8.5%), resin dispersion (8.5%) and polydimethylsiloxane (16.5%) were from the 12 isolated items. The higher rate of microplastics ingestion observed in smaller clam size M. lyrata and similar rate between weather season (dry season and wet season) indicate that these contaminated seafood increases the human exposure through consumption. The type of polymer identified in this study indicate that most of the microplastic may sources from human daily products.